Justification of choice of material and technology for aramid fiber-based polymer composite manufacturing - Solovyov, V. V.; Rychkova, A. D.; Neretina, A. S. (Космические аппараты и технологии, 2025)
The use of composite materials, especially in space technology, is becoming increasingly relevant due to their unique properties, which make it possible to function effectively in extreme conditions and maintain specified characteristics. The article presents a study of polymer composite materials based on aramid fibers and their applications in the rocket and space industry. The purpose of the study is to substantiate the possibilities of creating such composites and to assess their prospects for use in spacecraft. The paper defines the key physical and mechanical properties of aramid fibers and the effect of these properties on the characteristics of composite materials based on an epoxy matrix. The analysis of polymer composite manufacturing technologies with comparative characteristics of various matrices, fillers and production methods is also carried out. The results obtained confirm the high potential and expediency of using aramid-epoxy composites in rocket and space technology due to their high strength, lightness and resistance to aggressive environments. For reliable applications, an in-depth study of the stability and durability of such materials in outer space is necessary. Further research should cover aspects such as impact resistance and thermal stability to ensure the safety and reliability of future spacecraft designs. Использование композиционных материалов, особенно в космической технике, становится все более актуальным благодаря их уникальным свойствам, которые позволяют эффективно функционировать в экстремальных условиях и сохранять заданные характеристики. В статье представлено исследование полимерных композиционных материалов на основе арамидных волокон и их применение в ракетно-космической промышленности. Цель исследования заключается в обосновании возможностей создания таких композитов и оценке их перспектив для использования в космических аппаратах. В работе определены ключевые физико-механические свойства арамидных волокон и влияние этих свойств на характеристики композиционных материалов на основе эпоксидной матрицы. Также проведен анализ технологий изготовления полимерных композитов со сравнительной характеристикой различных матриц, наполнителей и методов производства. Полученные результаты подтверждают высокий потенциал и целесообразность применения арамидно-эпоксидных композитов в ракетно-космической технике благодаря высокой прочности, легкости и устойчивости к агрессивным средам. Для надежного применения необходимо углубленное исследование устойчивости и долговечности таких материалов в космическом пространстве. Дальнейшие исследования должны охватывать такие аспекты, как ударная стойкость и термическая стабильность, чтобы гарантировать безопасность и надежность будущих конструкций космических летательных аппаратов.